Implementação prática de um controlador preditivo a um processo não-linear - Gonçalves, Daniel (2012)
The standardization of operational procedures in chemical plants through the use of automation have became a mandatory practice for the current companies that tries or have tried a place in the commodities competitive stock. Real gains in productivity and recovery are closely related to controller s performance used in chemical process of this companies. There are a several controllers strategies in which the predictive control is a powerful tool that shows attractive results. The use of predictive control is achieved by the implementation of the control strategy in a pilot plant of a MIMO (Multiple-Input Multiple-Output) non-linear process. The nonlinear process is a experimental system of a neutralization reactor with three input flows and one output flow, and the manipulated variable are the level of reactor and the pH of mixture. The input flows are one of acid, one of base and one of buffer solution and this are the controlled variables. The information used to controller project was obtained in a open loop procedure. In this procedure, it was made disturbances in input variable and watched the output variable behavior. The MPC ( Model Predictive Control) performance was tested in a simulation and after in the pilot plant. The results achieved in simulation and practice implementation shows the excellent performance of controller to the process.